2017
DOI: 10.1080/07420528.2017.1356840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differences in the availability of light upon the circadian rhythms of institutionalized elderly

Abstract: The aim of this study was to compare the availability of diurnal and nocturnal light in two residences for aged persons (R1 and R2, Palma de Mallorca, Illes Balears, Spain). We found that the R1 inmates were exposed to lower amounts of light during waking time and higher amounts during sleeping time. The main traits of the circadian rhythms and the quality of sleep in the inmates of the two residences were found to be positively related to the availability of light during waking time and negatively to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Conversely, the values of light during night-time were much higher (40 lux/10 min), because of the institutional established routines, in contrast with the recommended 5 lux levels. Most likely, the exposure to light during sleep exacerbates the already diminished age-related levels of melatonin (Wu et al, 2003(Wu et al, , 2007Wu and Swaab, 2005) and reduces diurnal-nocturnal light contrast (Rubiño et al, 2017). Consequently, the subjects selected were ideally suited to study the effect of BLT, which, applied during morning time, improves the activity of the SCN clock, which is extremely sensitive to deficits in morning light (Minors et al, 1991;Rüger et al, 2013), and improving the cognitive, functional and clinical variables (Mishima et al, 1994;Dowling et al, 2008).…”
Section: Discussion Lightmentioning
confidence: 99%
“…Conversely, the values of light during night-time were much higher (40 lux/10 min), because of the institutional established routines, in contrast with the recommended 5 lux levels. Most likely, the exposure to light during sleep exacerbates the already diminished age-related levels of melatonin (Wu et al, 2003(Wu et al, , 2007Wu and Swaab, 2005) and reduces diurnal-nocturnal light contrast (Rubiño et al, 2017). Consequently, the subjects selected were ideally suited to study the effect of BLT, which, applied during morning time, improves the activity of the SCN clock, which is extremely sensitive to deficits in morning light (Minors et al, 1991;Rüger et al, 2013), and improving the cognitive, functional and clinical variables (Mishima et al, 1994;Dowling et al, 2008).…”
Section: Discussion Lightmentioning
confidence: 99%
“…Lighting interventions providing circadian-effective light exposures have shown great promise as a nonpharmacological treatment to help regulate sleep in populations at risk for circadian rhythm disruption, such as persons living with Alzheimer’s disease and related dementias. Studies have demonstrated that daytime light exposure can consolidate and increase nighttime sleep efficiency, while increasing daytime wakefulness and reducing evening agitation in this population ( Figueiro et al, 2014 , 2015 , 2016 , 2019 , 2020 ; Figueiro, 2017 ; Rubiño et al, 2017 , 2020 ). Similar light therapy approaches have been shown to improve mood outcomes, perhaps via improved circadian entrainment, in patients undergoing autologous stem cell transplantation hospitalization for the treatment of multiple myeloma ( Valdimarsdottir et al, 2018 ).…”
Section: Hospital Light Interventions For Sleep and Circadian Healthmentioning
confidence: 99%
“…Second, nursing home residents are often exposed to less daylight during the day, which is necessary for good sleep health. A study in Spain investigated the relationship between access to daylight and circadian rhythm in two nursing homes and reported that the residents of the nursing home with more daylight and wider windows had a healthier circadian rhythm, better sleep quality, and improved autonomic function than those living in rooms with less daylight and limited window spaces [ 72 ]. The mean daylight exposure for 66 aging adults was 485 lux (SD = 761), 17% of aging adults living in a nursing home were never exposed to light (combined daylight and artificial light) greater than 1000 lux and 26% of patients were not exposed to any light greater than 2000 lux [ 73 ].…”
Section: Resultsmentioning
confidence: 99%